The role of diffuse correlation spectroscopy and frequency-domain near-infrared spectroscopy in monitoring cerebral hemodynamics during hypothermic circulatory arrestsCentral MessagePerspective - Alexander I. Zavriyev, BS; Kutlu Kaya, MS; Parisa Farzam, PhD; Parya Y. Farzam, BS; John Sunwoo, PhD; Arminder S. Jassar, MBBS; Thoralf M. Sundt, MD; Stefan A. Carp, PhD; Maria Angela Franceschini, PhD; Jason Z. Qu, MD (JTCVS Techniques)
Objectives: Real-time noninvasive monitoring of cerebral blood flow (CBF) during surgery is key to reducing mortality rates associated with adult cardiac surgeries requiring hypothermic circulatory arrest (HCA). We explored a method to monitor cerebral blood flow during different brain protection techniques using diffuse correlation spectroscopy (DCS), a noninvasive optical technique which, combined with frequency-domain near-infrared spectroscopy (FDNIRS), also provides a measure of oxygen metabolism. Methods: We used DCS in combination with FDNIRS to simultaneously measure hemoglobin oxygen saturation (SO2), an index of cerebral blood flow (CBFi), and an index of cerebral metabolic rate of oxygen (CMRO2i) in 12 patients undergoing cardiac surgery with HCA. Results: Our measurements revealed that a negligible amount of blood is delivered to the cerebral cortex during HCA with retrograde cerebral perfusion, indistinguishable from HCA-only cases (median CBFi drops of 93% and 95%, respectively) with consequent similar decreases in SO2 (mean decrease of 0.6 ± 0.1% and 0.9 ± 0.2% per minute, respectively); CBFi and SO2 are mostly maintained with antegrade cerebral perfusion; the relationship of CMRO2i to temperature is given by CMRO2i = 0.052e0.079T. Conclusions: FDNIRS-DCS is able to detect changes in CBFi, SO2, and CMRO2i with intervention and can become a valuable tool for optimizing cerebral protection during HCA.